Effects of peeling methods on the quality of cubiu fruits - Caceres,Luty Gomez (2012)
Cubiu (Solanum sessiliflorum Dunal) is an Amazonian Basin native fruit. Its importance comes from its high contents of pectin. Currently, processing technologies are necessary for the substitution of the traditional system (small crops and small-scale processing) for a larger scale system and thus increase the use of biodiversity and promote the implementation of Local Productive Arrangements of agribusiness in the Amazon. This research aims to evaluate the methods of peeling cubiu. Ripe fruits were divided into lots (150 each) and subjected to the following treatments: immersion in 2.5% NaOH boiling solution for 5 minutes, exposure to water vapor, and immersion in water at 96 ºC for 5, 10, 15 and 20 minutes. The peel released during heat treatment and immediately removed under running tap water. In the control treatment, the fruits were manually peeled (unheated) with a stainless steel knife. The treatments were evaluated for completeness and ease of peeling, tissue integrity, texture, and peroxidase activity. The immersion in 2.5% NaOH boiling solution (5 minutes) stood out as the best treatment since it inhibited the enzymatic browning and intensified the natural yellow color of the cubiu fruit and easily and fully peeled the whole fruit more rapidly without damaging its tissues. This treatment was chosen as the most advantageous because it can promote simultaneous peeling and bleaching. Therefore, it is recommended for cubiu industrial processing.